Fluvial biofilm responses to joint changes in nutrients, temperature, turbidity and water velocity: an ex situ experiment - Cochero, Joaquín (2016)
Fil: Cochero, Joaquín. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Instituto de Limnología Dr. Raúl A. Ringuelet; Argentina